Surprising migration and population size dynamics in ancient Iberian brown bears (Ursus arctos) - Valdiosera, CE; Garcia-Garitagoitia, JL; Garcia, N; Doadrio, I; Thomas, MG; Hanni, C; Arsuaga, JL; Barnes, I; Hofreiter, M; Orlando, L; Gotherstorm, A (NATL ACAD SCIENCES, 2008)
The endangered brown bear populations (Ursus arctos) in Iberia have been suggested to be the last fragments of the brown bear population that served as recolonization stock for large parts of Europe during the Pleistocene. Conservation efforts are intense, and results are closely monitored. However, the efforts are based on the assumption that the Iberian bears are a unique unit that has evolved locally for an extended period. We have sequenced mitochondrial DNA (mtDNA) from ancient Iberian bear remains and analyzed them as a serial clataset, monitoring changes in diversity and occurrence of European haplogroups over time. Using these data, we show that the Iberian bear population has experienced a dynamic, recent evolutionary history. Not only has the population undergone mitochondrial gene flow from other European brown bears, but the effective population size also has fluctuated substantially. We conclude that the Iberian bear population has been a fluid evolutionary unit, developed by gene flow from other populations and population bottlenecks, far from being in genetic equilibrium or isolated from other brown bear populations. Thus, the current situation is highly unusual and the population may in fact be isolated for the first time in its history.